Steve Sabella: Independence - Faruqi, Samar; Horsman, Meagan Kelly; Preston, Madeline Yale; Sabella, Steve (Dubai; Meem Gallery, 2014)
Exhibition catalog. Oct-Dec 2014.
English
Keywords: N4390-5098 Visual Arts- Exhibitions